2011
DOI: 10.1074/jbc.m111.265413
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Basis for the Interaction of Low Density Lipoprotein Receptor-related Protein 1 (LRP1) with Integrin αMβ2

Abstract: The LDL receptor-related protein 1 (LRP1) is a large endocytic receptor that controls macrophage migration in part by interacting with ␤ 2 integrin receptors. However, the molecular mechanism underlying LRP1 integrin recognition is poorly understood. Here, we report that LRP1 specifically recognizes ␣ M ␤ 2 but not its homologous receptor ␣ L ␤ 2 . The interaction between these two cellular receptors in macrophages is significantly enhanced upon ␣ M ␤ 2 activation by LPS and is mediated by multiple regions in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
34
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 48 publications
(45 reference statements)
1
34
0
Order By: Relevance
“…Indeed, Spijkers and colleagues have described a complex formation between LRP-1 and ␤2-integrin by using recombinant proteins and showed that LRP-1 inhibition is associated with impaired ␤2-dependent adhesion to endothelial cells (51). In our study, the use of LRP-1 minireceptors revealed that the fourth ligand binding cluster of LRP-1 is involved in CD44 binding, as previously mentioned for ␤2-integrins (46,51). LRP-1 was also described to mediate the uptake of integrin-containing complexes in macrophages to facilitate the cellular detachment at the rear of the cell (7).…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Indeed, Spijkers and colleagues have described a complex formation between LRP-1 and ␤2-integrin by using recombinant proteins and showed that LRP-1 inhibition is associated with impaired ␤2-dependent adhesion to endothelial cells (51). In our study, the use of LRP-1 minireceptors revealed that the fourth ligand binding cluster of LRP-1 is involved in CD44 binding, as previously mentioned for ␤2-integrins (46,51). LRP-1 was also described to mediate the uptake of integrin-containing complexes in macrophages to facilitate the cellular detachment at the rear of the cell (7).…”
Section: Discussionsupporting
confidence: 56%
“…Cao and colleagues have proposed an exciting molecular model in macrophages in which LRP-1 facilitates cell detachment at the trailing edge by mediating the internalization of integrin-containing adhesion complexes (7). Cooperation at the cell surface between LRP-1 and ␤2-integrin was also reported to mediate the adhesion of leukocytes (46,51). The main distribution of LRP-1 at the leading edge and at the rear of the cell could therefore orchestrate cell polarization and support directional migration of various cell types (7,8).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Mac-1 deficient macrophages (mice lacking integrin ␣M) did not exit the peritoneal cavity in the accelerated exiting model (17), although we observed more rapid exiting in the same model with mice lacking integrin ␤2. Outside-in signaling (29) and binding to low density lipoprotein receptor-related protein (LRP)-1, which is required for migration (30), are both impaired in the absence of integrin ␣M. Thus, although Mac-1 null mice still express ␣X␤2 that could mediate fibrin binding, their macrophages would be impaired in "outside-in" signaling from fibrin.…”
Section: Discussionmentioning
confidence: 99%
“…3 Relevant to the current study, low-density lipoprotein receptorrelated protein 1 (LRP-1) has previously been described as being associated with the I-domain of the a-chain of the b 2 integrin macrophage antigen-1 (Mac-1) 5 and being required for integrin clustering and adhesion of the monocytic cell line U937. 6 Using pharmacologic inhibition, the authors provide evidence that LRP-1 is the receptor for MK on neutrophils because blockade of this receptor inhibited the MK-mediated LFA-1 high-affinity conformation and neutrophil adhesion in vitro.…”
mentioning
confidence: 99%